Law Enforcement to Copyright Infringement of Songs on the Internet Media - Andrew Shandy Utama (Universitas Lampung, 2018)
Initially, the scope of Copyright protection only focuses on creative works that are manifested in real terms. The development and advancement of technology make the scope of Copyright protection experience an expansion not only in copyrighted works that are realized in a real form but also protect copyrighted works that are digitized on internet media. The problem discussed in this research is how law enforcement to Copyright infringement of songs on the internet media is? The method used in this research is normative legal research using the regulatory approach. The results of this research indicate that the development and advancement of technology can facilitate the dissemination of songs in MP3 format uploaded on internet media. To prevent the occurrence Copyright infringement of songs on the internet media, in Law Number 28 of 2014 has been stipulated strict criminal sanctions for anyone without permission who has violated the Copyright, especially the economic rights of the owner. Keywords: Copyright, Internet Media, Law Enforcement